P459 Hospitalization, use of biologics and surgery rates in inflammatory bowel diseases: a single-center comparative analysis between public and private healthcare systems in a tertiary unit from Latin America. (30th January 2023) - Zacharias, P; Perussolo, M; Magro, D O; Barauna, F D S B; Kotze, P G
Abstract: Background: Inflammatory bowel diseases (IBD), Crohn's disease (CD) and ulcerative colitis (UC), characterized by chronic inflammation of the intestine, have a rising incidence and prevalence globally. The potential impact of socioeconomic inequality on health and mortality is well documented. In chronic diseases, the effect of inequality in assessment to healthcare can be associated with a higher frequency of complications and worse organ functionality in patients with social deprivation. In IBD, there are scarce studies comparing the differences between patients according to their socioeconomic status. Our aim was to comparatively evaluate hospitalizations, use of biologics and rates of surgery in patients with IBD between public and private healthcare systems. Methods: single-center retrospective cohort study in patients with IBD from a tertiary referral unit from Latin America, between 2015 and 2021. CD and UC patients were classified into two subgroups: public and private healthcare systems. Main analyzed variables were age at diagnosis, gender, Montreal classification, new diagnoses or referred patients, smoking status, previous medications, need for IBD-related hospitalizations and abdominal surgery. Demographic characteristics, hospitalizations, need for surgery and biologics were compared between two subgroups: private and public healthcare systems. Results: 500 patients were included, 322 with CD and 178 with UC. CD-related hospitalizations were frequently observed in both healthcare systems (76.28% in private and 67.46% in public). More than half of the patients had been submitted to one or more CD-related abdominal surgical procedure, with no significant difference between the subgroups. Although there was no difference in the rates of use of biological therapy in CD subgroups, infliximab was more used in the public setting (57.69% vs. 43.97%, p=0.014). There was no difference in UC-related hospitalizations between the subgroups (public 30.69% and private 37.66%, p=0.33) as well as the rates of colectomy (public: 16.83%, private: 19.48%, p=0.65). Biologics were used almost twice as often in private as compared to the public system (45.45% vs. 22.77%, p=0.001). Conclusion: Patient demographics were overall similar between healthcare systems in IBD patients. There were no differences in the rates of hospitalization and abdominal surgery between the two subgroups in both diseases. In patients with UC, there was greater use of biological therapy in the private healthcare setting. Global data regarding the possible impact of social deprivation in IBD-related outcomes are warranted.